Performance Evaluation of Depth Adjustment and Void Aware Pressure Routing (DA-VAPR) Protocol for Underwater Wireless Sensor Networks. (6th November 2019) - Ganesh, N
Abstract: Underwater wireless sensor network (UWSN) has gained its popularity as a powerful technology for monitoring oceans, sea and river. The sensor node drifting along with ocean current offers 4D (space and time) monitoring for real-time underwater application. However, the main challenge arises from the underwater acoustic communication that results in high propagation delay, packet loss and overhead in the network. In order to overcome these issues, a depth adjustment and void aware pressure routing protocol is proposed for UWSN. A greedy forwarding strategy is used to forward the packet. In case a node fails to forward the packet using greedy forwarding strategy, then it immediately switches to the recovery mode. In the recovery mode, the node determines the new depth using particle swarm optimization technique. The global best value gives the new depth with minimum displacement. The void node forwards the packet with minimum displacement without any packet loss and delay.